Exploring the Diversity and Biotechnological Potential of Cultured and Uncultured Coral-Associated Bacteria - Caren Leite Spindola Vilela (MDPI AG, 2021)
Coral-associated microbes are crucial for the biology of their hosts, contributing to nutrient cycling, adaptation, mitigation of toxic compounds, and biological control of pathogens. Natural products from coral-associated micro-organisms (CAM) may possess unique traits. Despite this, the use of CAM for biotechnological purposes has not yet been adequately explored. Here, we investigated the production of commercially important enzymes by 37 strains of bacteria isolated from the coral species Mussismilia braziliensis, Millepora alcicornis, and Porites astreoides. In-vitro enzymatic assays showed that up to 56% of the isolates produced at least one of the seven enzymes screened (lipase, caseinase, keratinase, cellulase, chitinase, amylase, and gelatinase); one strain, identified as Bacillus amyloliquefaciens produced all these enzymes. Additionally, coral species-specific cultured and uncultured microbial communities were identified. The phylum Firmicutes predominated among the isolates, including the genera Exiguobacterium, Bacillus, and Halomonas, among others. Next-generation sequencing and bacteria culturing produced similar but also complementary data, with certain genera detected only by one or the other method. Our results demonstrate the importance of exploring different coral species as sources of specific micro-organisms of biotechnological and industrial interest, at the same time reinforcing the economic and ecological importance of coral reefs as reservoirs of such diversity.